Life expectancy and claiming behavior in a flexible pension system - Dennis Fredriksen; Christian N. Brinch; Ola L. Vestad (Statistics Norway, Research Department, 2017)
We study the relationship between early claiming of pensions and incentives in the highly flexible Norwegian public pension system, measuring incentives to claim based on an estimated model for expected longevity. Despite a strong correlation between incentives and claiming decisions, the additional costs to public budgets arising from this selection turn out to be modest. Based on analyses exploiting only variation in expected pensions generated by variation in parental longevities and only claiming of pensions not in conjunction with retirement, we conclude that part of the selection is active: Some individuals claim pensions early because they gain from doing so.
Keywords: H55; J14; J26; 330; social security; pension benefits; retirement; annuity